Matemática financeira para o ensino fundamental II: uma sequência didática para o ensino que promova pequenos empreendedores - Brito, Augustinho Neto Saraiva (Universidade Federal do Tocantins, 2021)
Mathematics as a curricular component must guarantee stimulation, creativity, and critical thinking; at the same time, entrepreneurship must provide elements for the student’s cultural change. In this perspective, thinking about the teaching of Financial Mathematics in the last phase of Elementary School, in the training of entrepreneurs, and in the improvement of social conditions, what pedagogical actions can be recommended? This work had a general objective: to propose a didactic sequence for the teaching of Financial Mathematics for students of the 9th year of Elementary School, promoting and encouraging the creation and development of small entrepreneurs, in addition to financial practices beneficial to their quality of life. The method used consisted of exploratory research, through semi-structured interviews via audio conference for data collection, carried out with Banco da Amazônia clients who contracted microcredit operations in 2019, in Araguaína, in the state of Tocantins. The analysis of the data revealed the need to implement actions that help teachers from the 9th grade of an Elementary School in the insertion of themes related to Financial Mathematics, entrepreneurship, and microcredit. In this context, the objective of this study was fulfilled, generating a didactic sequence for teachers to have ideas on how to work in Financial Mathematics, with suggestions for activities that promote and encourage the training of small entrepreneurs and financial practices, also contributing to the good social welfare of families.